Molecular Doping Increases the Semitransparent Photovoltaic Performance of Dilute Bulk Heterojunction Film with Discontinuous Polymer Donor Networks. Issue 4 (9th February 2022) - Tang, Yabing; Zheng, Hong; Zhou, Xiaobo; Tang, Zheng; Ma, Wei; Yan, Han
Abstract: The semitransparent and colorful properties of organic solar cells (OSCs) attract intensive academic interests due to their potential application in building integrated photovoltaics, wearable electronics, and so forth. The most straightforward and effective method to tune these optical properties is varying the componential ratio in the blend film. However, the increase in device transmittance inevitably sacrifices the photovoltaic performance because of severe carrier recombination that originates from discontinuous charge‐transport networks in the blend film. Herein, a strategy is proposed via the molecular‐doping strategy to overcome these shortcomings. It is discovered that p‐doping is able to release the trapped holes in segregated polymer domains leading to short‐circuit current enhancement, while n‐doping is more effective to fill the bandgap states producing a higher fill factor. More importantly, either type of doping improves the photovoltaic performance in the semitransparent photovoltaic devices. These discoveries provide a new pathway to breaking the compromise between the photovoltaic performance and optical transmittance in semitransparent OSCs, and hold promise for their future commercialization. Abstract : Varying the blend ratio is effective to tune the optical properties of a bulk heterojunction (BHJ) film for future application in semitransparent organic solar cells (OSCs). It is discovered that either type of doping helps overcome the discontinuous charge‐transport network‐led carrier recombination in dilute BHJ films. This discovery provides a new methodology to reduce the electrical–optical gap of semitransparent OSCs.